608 Temporomandibular disorders, occlusal splints, and treatment options: a survey-based investigation (Balneo and PRM Research Journal, 2024)
Background: The term "temporomandibular disorders" (TMDs) refers to a group of painful conditions that affect both the hard and soft orofacial anatomical structures. The primary objectives of TMD treatment are to lessen pain and enhance mandibular movements, re-establishing proper functioning. One of the widely used treatment options is represented by the occlusal splint, a non-invasive intraoral device, which determines muscle relaxation and repositions the temporomandibular joint structures in a reversible manner. The study aimed at assessing the efficacy of occlusal splints for the treatment of temporomandibular disorders (TMDs). Methods: Twenty-six patients, nineteen of whom were female and seven of whom were male, ranging in age from twenty to seventy, met the criteria needed to take part in this study.  Two different questionnaires were employed, a patient-focused and a clinician-focused questionnaire. The patient's data encompassed general health status as well as TMD signs and symptoms, whereas the clinician's questions addressed assessment and treatment alternatives, including the particularities of occlusal splint therapy. Results: The majority of the patients were diagnosed with disc displacement with reduction (61.5%), followed by myalgia (26.9%). The only form of treatment preferred by physicians was the Michigan occlusal splint, which was mainly used on the maxillary dental arch (84,6%). After the splint therapy was completed and the intended results were obtained, the treatment plan was finished using selective grinding, prosthetic dental restorations, orthodontic therapy, or a combination of these procedures. The patient was required to continue physical therapy (7,7%), wear a full-arch night guard (42.3%), and undergo rigorous periodic control sessions (34.6%) to maintain the final aesthetic and functional results. Conclusions: Occlusal splints are an efficient and reliable initial therapy preference for patients with temporomandibular disorders. In addition to improving symptoms in the temporomandibular joint, occlusal splints may determine mandibular repositioning, which also implies a variety of treatment approaches, ranging from the minimally invasive to the most complex, to achieve a functional occlusal status.